Constructing community in the Neolithic of southern Jordan: Quotidian practice in communal architecture. - Cheryl A Makarewicz; Bill Finlayson (PLoS ONE)
The emergence of food production during the earliest Neolithic of the Near East was accompanied by profound changes in the ways in which societies were organized. Elaborate and multi-stage mortuary practices involving the removal, caching, and plastering of symbolically charged skulls are thought to have played an important role in cross-cutting household lines to integrate communities and maintain social cohesion during the late tenth to ninth millennium cal BP, particularly in Middle Pre-Pottery Neolithic B settlements located in the southern Levant. While the ritual and mortuary activities associated with skull manipulation were dramatic and high impact occasions that drew people and households together, it is likely they were highly episodic and, consequently, attendant community cohesion susceptible to decay over time. Recent research in southern Jordan, where skull plastering was not practiced as seen elsewhere in the southern Levant, has revealed that non-residential building structures were a common feature of early Pre-Pottery Neolithic settlements. Renewed excavations at Beidha, a Middle PPNB settlement located in the Shara'a mountains, have revealed a large, easily accessible communal structure that provided a focal point in which mundane, informal daily activities could regularly take place. The routine and repeated interactions fostered by such non-domestic structures facilitated highly durable modes of community cohesion and was part of a temporally deep ethos of community that first emerged a thousand years earlier when people first began to experiment with plant cultivation. It appears that in southern Jordan, a distinctive social cohesion pathway developed that engaged community daily practice within non-residential buildings to maintain and strengthen social structures, rather than occasional and dramatic ritual and mortuary practices used elsewhere in the southern Levant.